Mobilizing science and technology to address development deficits in low-and middle-income countries - International Livestock Research Institute (International Livestock Research Institute, 2021)
Ameenah Gurib-Fakim, former president of Mauritius, speaks of the importance of higher education for the youth of Africa in mobilizing science and technology to address development deficits in African economies. This video was recorded 16 March 2021 during an online event that also announced the 2020 ILRI CapDev Grand Challenge winners.